2023
DOI: 10.1186/s40779-023-00469-5
|View full text |Cite
|
Sign up to set email alerts
|

The marriage of immunomodulatory, angiogenic, and osteogenic capabilities in a piezoelectric hydrogel tissue engineering scaffold for military medicine

Ping Wu,
Lin Shen,
Hui-Fan Liu
et al.

Abstract: Background Most bone-related injuries to grassroots troops are caused by training or accidental injuries. To establish preventive measures to reduce all kinds of trauma and improve the combat effectiveness of grassroots troops, it is imperative to develop new strategies and scaffolds to promote bone regeneration. Methods In this study, a porous piezoelectric hydrogel bone scaffold was fabricated by incorporating polydopamine (PDA)-modified ceramic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…Angiogenesis is important for bone regeneration because of oxygen and nutrient transportation by neoformative blood vessels [ [59] , [60] , [61] ]. It has been reported that the administration of intermittent PTH1-34 promoted vascularization in fracture callus [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Angiogenesis is important for bone regeneration because of oxygen and nutrient transportation by neoformative blood vessels [ [59] , [60] , [61] ]. It has been reported that the administration of intermittent PTH1-34 promoted vascularization in fracture callus [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Piezoelectric ceramics such as lead zirconate titanate, barium titanate (BT), zinc oxide, potassium potassium niobate, hydroxyapatite (HA), sodium lithium niobate, and boron nitride nanotubes have significant advantages in terms of piezoelectric coefficients, but what deserves the attention of all researchers is that piezoelectric ceramics continue to release various types of ions within biological fluids, and these ions can produce varying degrees of cytotoxicity ( Rajabi et al, 2015 ; Tandon et al, 2018 ). After doping with 10% BT and 10% HA, an output voltage of 0.8 V can be detected on the hydrogel film ( Wu et al, 2023 ). Moreover, due to the non-degradability and high elastic modulus of piezoelectric ceramic-based tissue engineering scaffolds, most of these materials are doped into various types of polymers or ceramics in the form of piezoelectric particles in order to utilize their excellent piezoelectric properties ( Baxter et al, 2009 ; Bagchi et al, 2014 ).…”
Section: Piezoelectric Biomaterialsmentioning
confidence: 99%
“…Results from in vivo subcutaneous and femoral condyle implantation models revealed reduced expression of iNOS and increased expression of CD206 cells, thus confirming the piezoelectric generated electric field mediated macrophage polarization from M1 to M2. Similarly, Wu et al in 2023 prepared the self-powered piezoelectric nanogenerator (PENG) based on PDA-modified BaTiO 3 nanoparticles into a chitosan/gelatin (Cs/Gel) matrix which generated 0.8 V under 1 kPa pressure and resulted in M2 polarization for enhancing bone regeneration …”
Section: Types Of Electrical Stimulation Sources For Immunomodulationmentioning
confidence: 99%